The relation of the frequency and functional molecules expression on plasmacytoid dendritic cells to postpartum hepatitis in women with HBeAg-positive chronic hepatitis B virus infection - Wang, Fuchuan; Song, Meiying; Hu, Yuhong; Yang, Liu; Bi, Xiaoyue; Lin, Yanjie; Jiang, Tingting; Deng, Wen; Wang, Shiyu; Sun, Fangfang; Zeng, Zhan; Lu, Yao; et al. (Frontiers in Immunology, 2022)
Objective: To explore the correlation between postpartum hepatitis and changes of plasmacytoid dendritic cells’ (pDC) function and frequency in hepatitis B e antigen (HBeAg)-positive pregnant women with chronic hepatitis B virus (HBV) infection. Methods: Pregnant women with chronic HBV infection receiving antiviral treatment (treated group) or not receiving antiviral treatment (untreated group) were enrolled and demographic information was collected before delivery. Clinical biochemical, virological serology, pDC frequency and functional molecular expression were tested before delivery and at 6, 12, 24 weeks after delivery. Results: 90 eligible pregnant women were enrolled, 36 in the untreated group and 54 in the treated group. 36 patients developed postpartum hepatitis, including 17 (17/36, 47.2%) in the untreated group and 19 (19/54, 35.2%) in the treated group (2=1.304 p=0.253), and 22 cases of hepatitis occurred at 6 weeks postpartum, 12 at 12 weeks postpartum, and 2 at 24 weeks postpartum. The alanine transaminase (ALT) levels at any time postpartum were significantly higher than that of the antepartum, especially at 6 weeks and 12 weeks postpartum. However, the frequencies of pDCs, CD83+ pDCs and CD86+ pDCs antepartum had no significant difference from any time postpartum. The frequencies of CD83+ pDCs, CD86+ pDCs in the treated group antepartum were significantly higher than those in the untreated group [12.70 (9.46, 15.08) vs. 10.20 (7.96, 11.85), p=0.007; 22.05 (19.28, 33.03) vs. 18.05 (14.33, 22.95), p=0.011], and the same at 12 weeks postpartum [12.80 (10.50, 15.50) vs. 9.38 (7.73, 12.60), p=0.017; 22.50 (16.80, 31.20) vs. 16.50 (12.65, 20.80), p=0.001]. The frequency of CD86+ pDCs in the treated group was significantly higher than that in the untreated group at 24 weeks postpartum [22.10 (16.70, 30.00) vs. 17.10 (13.70, 20.05), p=0.006]. Conclusions: Postpartum hepatitis in HBV infected women mainly occurs at 6-12 weeks postpartum. Antiviral treatment during pregnancy can significantly increase the frequencies of CD83+ pDCs and CD86+ pDCs in pregnant women with chronic HBV infection.